Effects of palm oil derived tocotrienol rich fraction and vitamin e isomers on biomarkers of early atherogenesis in stimulated human umbilical vein endothelial cells - Suhaila Abd Muid,; Froemming, Gabriele Anisah Ruth,; Abd Manaf Ali,; Thuhairah Hasrah Abdul Rahman,; Zalina Hamid,; Hapizah Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study was conducted to investigate the effects of tocotrienol rich fraction (TRF), α-TOC, and pure TCT isomers (α-. γ- & δ-TCT) on inflammation, endothelial activation, nuclear factor kappa B (NFκB), endothelial nitric oxide synthase (eNOS) and monocyte binding activity (MBA) in vitro. Human umbilical vein endothelial cells (HUVECs) were incubated with various concentrations of α-TOC, pure TCT isomers and TRF (0.3-10 μM) together with lipopolysaccharides (LPS) for 16 h. Culture medium and cells were collected and measured for the protein and gene expression of IL-6, TNF-α, NFκB, ICAM-1, VCAM-1, e-selectin, and eNOS. Monocyte binding activity (MBA) was measured by Rose Bengal staining. Area under the curve (AUC) analysis revealed that TRF and pure TCT particularly γ- and δ- isomers, showed better inhibition of inflammation and endothelial activation, MBA and greater eNOS increment than α-TOC. These suggest that TRF and pure TCT isomers have potential as preventive anti-atherogenic agents by attenuating the release of early biomarkers of atherogenesis which is better than α-TOC in LPS-stimulated human endothelial cells.